Sustainability with a Cost Perspective -- Driving the Industry to Embrace Sustainable Thinking - Windmark, Christina; Ericson Oberg, Anna; Winroth, Mats; Almstrom, Peter; Kurdve, Martin; Andersson, Carin (Journal of Environmental Accounting and Management, 2026)
Previous research has shown that sustainable improvements need incentives to carry them through. An assumption is that it may be easier to incorporate sustainable thinking in an organization if the organization understands which actions it is that are having a positive effect on sustainability and on tangible costs. This paper aims to highlight the synergy effects that occur in the intersection between production costs, performance and sustainable improvements and to present a possible way of modelling these effects. The study has used three methods of analysis: literature review, a web survey sent to representatives in the Swedish manufacturing industry, and economic simulations using a case study. The literature review and the survey are used to identify important costs and incentives for sustainable improvements. The study is limited to the production shop floor level, incorporating only aspects directly affecting, and affected by manufacturing operations. \par This paper takes a holistic approach to sustainability drivers, cost drivers in industry, and economic simulations, creating an overall insight. From the literature review and the survey, intersections between sustainability measures and cost drivers could be found in the areas of site-occupancy area/floor space, resource consumption, and efficiency. Apart from laws and regulations, economic aspects and management attention are perceived as the most important drivers, but also obstacles for sustainability improvements. The study aims to support industry to embrace sustainable thinking, presenting a quantitative method to visualize the synergy effects of sustainability and measurable improvements from production development, using performance measurements when estimating manufacturing costs. The possibility to connect manufacturing cost with environmental impact, through use of performance parameters is demonstrated in a case study; where the significant environmental and economic impact of rejections is analyzed for the machining of steel frames.